Triboelectric pad journal bearing for self-powered condition monitoring. (1st December 2022) - Gao, Mang; Li, Yahui; Choi, Junho
Abstract: With the widespread application of the Internet of Things (IoT) technology, smart fault detection and condition monitoring are urgently required in mechanical systems. The emergence of triboelectric nanogenerators (TENG) provides a novel strategy to achieve self-powered sensing, which can serve as an ideal candidate for the condition monitoring of bearings. In this study, a triboelectric pad journal bearing (T-PJB) was designed and fabricated to directly monitor the bearing condition. Through simulation, the geometrical structure of the T-PJB for high output was optimized, and the electrical performance was examined under various rotating conditions. The speed of the bearing shaft could be accurately measured using time- and frequency-domain methods. During the operation, faults caused by unbalanced forces were effectively identified based on the characteristics of the electrical output signals. Furthermore, the proposed T-PJB can be applied to monitor lubrication states because of its sensitive response to different lubrication conditions. Condition monitoring using the proposed T-PJB greatly contributes to reduced maintenance costs and long-term stable operation of various sliding bearings. Furthermore, the demonstrated smart T-PJB has promising feasibility in industrial applications for rotating machinery, establishing the foundation for smart plants. Graphical Abstract: ga1 Highlights: A smart T-PJB is proposed for machinery condition monitoring. Freestanding-mode TENG is constructed to characterize electrical signals. The self-powered triboelectric sensor shows great prospect in industrial application.